2022
DOI: 10.1186/s12871-022-01651-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound guided single shot costotransverse block (intertransverse process) in breast cancer surgery: a prospective, randomized, assessor blinded, controlled clinical trial

Abstract: Background Ultrasound guided costotransverse block (CTB) is a relatively new “peri-paravertebral” block that has been described recently. It has been previously reported that CTB, administered with a single high-volume injection, provides effective analgesia in breast conserving surgery. In this study we evaluated the effect of CTB when used in breast cancer surgery. Methods Seventy patients due to undergo breast cancer surgery were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…The insignificant influence of the ITP block with an absence of any measurable and clinically beneficial effects on postoperative opioid consumption in the current trial was highly unanticipated, contradicts previous findings10–12 16 17 and differs vastly from our initial hypothesis. Remarkably, although non-significant the placebo group had an overall decreased opioid consumption compared with the active group: we have no reason to believe that the blockade should cause exaggerated pain and we regard this, probably, as a chance finding.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The insignificant influence of the ITP block with an absence of any measurable and clinically beneficial effects on postoperative opioid consumption in the current trial was highly unanticipated, contradicts previous findings10–12 16 17 and differs vastly from our initial hypothesis. Remarkably, although non-significant the placebo group had an overall decreased opioid consumption compared with the active group: we have no reason to believe that the blockade should cause exaggerated pain and we regard this, probably, as a chance finding.…”
Section: Discussioncontrasting
confidence: 90%
“…Allegedly, the ITP block is effective in both breast cancer surgery and in video-assisted thoracoscopic surgeries8 9 with multiple-injection presumably advantageous in regard to dermatomal coverage12 in comparison to single injection 10. However, despite evidence that the ITP block is an opioid-sparing modality, the actual saved cumulated opioid quantity in various studies seems clinically inconsequential 11…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggested that the multi-injection ITPB could persistently block the dermatomes of T2–7 and provide effective analgesia for major breast cancer surgery. A recent study demonstrated that a single-injection ITPB at T3–4 using a mixture of 0.5% bupivacaine 15 mL plus 2% lidocaine 10 mL improved analgesic efficacy compared with no block in patients undergoing major breast cancer surgery 22. However, the analgesic improvement appeared to be marginal.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] I would like to use the term “costotransverse block” (CTB) for MICB to make it simple and for the correct understanding of the technique per se . The term CTB was used previously by Aygun et al [ 4 ] as they provided a single-shot block, in contrast to the multiple-level injections advocated by Nielsen et al ,[ 5 ] who described this technique first and named it “MICB”. The main purpose of this article is to clarify the difference between the two techniques, namely, the CTB and CTFB.…”
mentioning
confidence: 99%